Pengembangan Program Daily Physical Activity (DPA) Melalui Permainan Tradisional Pada Pembelajaran PJOK di Kelas V SDN Kebraon Surabaya - Agus Setiawan; Muhammad Muhyi; Yoso Wiyarno (Universitas PGRI Semarang, 2021)
This study aims to find out through the Daily Physical Activity (DPA) program to answer problems related to the fitness level of students. Developing the DPA program combined with traditional games makes it easier for teachers to implement the teaching and learning process, especially student fitness issues. The instruments in this study were using observation sheets, questionnaires, and TKJI. The results of the study were to determine the student's interest given by the researcher by providing DPA program through traditional games to students which aimed to determine student responses about the importance of maintaining physical fitness. The results of this study were 73%, so the student's response to the application DPA program through traditional games on student fitness was categorized as Good. From the results carried out in the field, the researchers did not only examine students' interest in learning PJOK through traditional games, they also found out about the fitness of students, namely through the TKJI test with the results that there was a significant model of the development of the Daily Physical Activity (DPA) program in learning PJOK through traditional games in class students V Kebraon I Elementary School Surabaya.Keywords: Daily Physical Activity, Traditional GamesAbstrakPenelitian ini bertujuan untuk mengetahui melalui program Daily Physical Activity (DPA) untuk menjawab permasalahan yang berkenan dengan tingkat kebugaran pada siswa. Pengembangan program DPA gabungan dengan permainan tradisional memudahkan pengajar dalam menerapkan proses belajar mengajar terutama masalah kebugaran siswa. Instrumen dalam penelitian ini yaitu menggunakan lembar observasi, angket, dan TKJI. Hasil dari penelitian untuk mengetahui minat siswa yang diberikan oleh peneliti dengan pemberian program DPA melalui permainan tradisional pada siswa yang bertujuan untuk mengetahui respon siswa tentang pentingnya menjaga kebugaran jasmani. Hasil dari penelitian ini yaitu 73%, maka respon siswa dengan penerapan program DPA melalui permainan tradisional terhadap kebugaran siswa dikategorikan Baik. Dari hasil yang dilakukan dilapangan peneliti tidak hanya meneliti tentang minat siswa pada pembelajaran PJOK melalui permainan tradisional juga mengetahui kebugaran siswa yaitu melalui tes TKJI dengan hasil terdapat yang signifikan model pengembangan program Daily Physical Activity (DPA) dalam pembelajaran PJOK melalui permainan tradisional pada siswa kelas V SDN Kebraon I Surabaya.Kata kunci: Daily Physical Activity, Permainan tradisional